Parental determinants of compliance with occlusion therapy for ambliopic children - Costa, Carla (2008)
Aims - Recent investigation studies apply to the fact that in spite of occlusive therapy about 1/3 of the amblyopic eyes don’t reach the visual acuity of 5/10. One of the reasons is the non-compliance with the treatment. The aim of this study is to evaluate the influence of psychosocial factors in the parental compliance of occlusive therapy in children with amblyopia and to determine the existence of significant differences between the Orthoptist’s recommendations, parental perception of these recommendations, and behaviour. Methods - To achieve the objective a Quantitative transversal study was delivered. Parents of amblyopic children (n=100) receiving occlusion therapy in a public hospital and a private clinic in Lisbon, participated in this study. Parents were asked to complete a questionnaire based on Roger’s Protection Motivation theory, also known as PMT. The parental variables analysed were severity, vulnerability, self-efficacy, behaviour intentions, perceived efficacy, and treatment barriers. Additionally, other variables were analysed such as parental perception of the occlusion prescription and parental behaviour. Results - The results show that 72% of the parents were complying with Orthoptist recommendations to patch their child against a percentage of 28% that didn’t comply. Perceived efficacy (p=0,011) and behaviour intention (p=0,015) were positively associated with compliance with therapy (!= 0,05). There is a positive mild correlation (kappa=0,536) between the Orthoptist’s recommendations and parental perception of these recommendations. There is a strong correlation (kappa=0,700) between the perception of hours of occlusion and the behaviour. Conclusions - It can be concluded that the perception of the benefits of recommended therapy provoked a coping response and the parental behaviour intention to comply with occlusive therapy. This means that the positive intention to go ahead with the treatment and the perceived efficacy in enhancing visual acuity may predict parental compliance. The compliance will be better if the parental perception of the adopted behaviour is associated with the better rehabilitation of their child, which was demonstrated in the current investigation.